2016
DOI: 10.25011/cim.v39i6.27508
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Beneficial Effects Of Hand And Foot Bathing On Vital Signs In Women With Caesarean Section

Abstract: Purpose: Hand-foot bathing therapy is a simple technique to induce sensations of comfort and relaxation. The aim of this study was to examine the effect of hand and foot bathing therapy on vital signs in women following caesarean section. Methods: Participants were sixty women with caesarean section. They divided to two groups: (1) study group (n=30, median age=26.67 years, SD=2.04); and, (2) control group (n=30, median age=27.75 years, SD=1.09). Vital signs were measured for 5 minutes before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…Based on the VAS scores, hand baths seemed to have provided subjective comfort and relaxation. This result was consistent with those reported in studies by Cal et al (), Miwa et al (), and Yamamoto et al (), which focused on the comfortable feeling of the hand bath.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the VAS scores, hand baths seemed to have provided subjective comfort and relaxation. This result was consistent with those reported in studies by Cal et al (), Miwa et al (), and Yamamoto et al (), which focused on the comfortable feeling of the hand bath.…”
Section: Discussionsupporting
confidence: 93%
“…The warm water (38–41°C) that is used in hand baths stimulates the thermoreceptors in the skin (Hall, ) and provides comfort and relaxation to the patient (Cal, Cakiroglu, Kurt, Hartiningsih, & Suryani, ; Saeki, ). In a previous study that investigated the implementation of hand baths in a Japanese hospital, >90% of the 229 nurses recognized their necessity, but the number of nurses that actually provided hand baths as part of their care was ≤18% (Miyashita & Yano, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the primary outcome immersion hands and feet in warm water can reduced postpartum perineal pain at 6 hours, (9) similar with Cal E et al reported that immersion hands and feet in warm water can reduced post caesarean delivery pain. (2) Steed CE et al was found the sympathetic nervous system can responsible for causing and maintenance pain via (7) increase pro-inammatory cytokine and Yamamoto K et al revealed that wrapped warm foot bath led to relaxation and increased parasympathetic activity.…”
Section: Discussionsupporting
confidence: 59%
“…Hands and feet warm bathing is simple technique that induce (7) sensation of comfort and relaxation .Duygu et al showed that warm water footbaths led to relaxation by increase parasympathetic response and decrease sympathetic (8) response . Cal E et al reported hands and feet warm bathing can reduce signicant postoperative caesarean delivery (9) pain . Now a day, there was no evidence of the immersion hands and feet in warm water for reduced postpartum vaginal delivery perineal pain.…”
Section: Introductionmentioning
confidence: 99%
“…Hand aromatherapy treatments for postpartum mothers increased their relaxation [24]. Hand and foot baths for women after cesarean section stabilized vital signs such as blood pressure and pulse [25]. In particular, it was suggested that necessary for postpartum mothers with previous diseases who are hospitalized to promote rest and relaxation.…”
Section: Care For Reducing Fatiguementioning
confidence: 99%